Evaluating Contextualized Content and Language Integrated Learning Materials at Tertiary Level - Wenhsien Yang (Universidad de La Sabana, 2019)
Evaluación de materiales de aprendizaje integrado de contenidos y lenguas extranjeras contextualizados a nivel de educación superior Avaliação de materiais de aprendizagem integrada de conteúdos e línguas estrangeiras contextualizados a nível de ensino superior The Content and Language Integrated Learning (CLIL) approach has been broadly adopted and extensively researched at different educational levels across European contexts. It is also becoming popular in Asian settings due to its dual focus on developing both language skills and content knowledge. It aims to empower learners with high mobility and employability in the globalized job market. However, successful implementation of CLIL in these countries has been difficult for various reasons, including lack of suitable CLIL-based curricular materials. This study reports how an English for Specific Purposes (ESP) teacher, who is also a CLIL practitioner, worked collaboratively with an English learner who has professional, industrial internship experience, to produce contextualized CLIL learning materials for tertiary education. It also examines to what extent the self-designed CLIL materials satisfy standards of good quality. In total, 47 English-major first-year students joined the study in a national polytechnic university in Taiwan. The results reveal that CLIL learners have a fairly high expectation of quality materials, and our design received 5%-25% lower agreement than the criteria. Moreover, learners' gender, language proficiency and previous secondary school major were factors that affected how they perceive the criteria of quality and our own CLIL materials. This demonstrates complexities of designing CLIL-based curricular materials addressing learners' individual differences (especially in terms of needs and expectations) in a polytechnic university with pedagogic implications. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Yang, W. (2018). Evaluating Contextualized Content and Language Integrated Learning Materials at Tertiary Level. LACLIL, 11(2), 236-274. DOI: 10.5294/laclil.2018.11.2.4 Received: 11/09/2018 Apporved: 30/11/2018